2020
DOI: 10.1186/s40842-020-00098-0
|View full text |Cite
|
Sign up to set email alerts
|

A study of glycemic variability in patients with type 2 diabetes mellitus with obstructive sleep apnea syndrome using a continuous glucose monitoring system

Abstract: Background: Obstructive sleep apnea syndrome (OSAS) in association with Type 2 Diabetes Mellitus (DM) may result in increased glycemic variability affecting the glycemic control and hence increasing the risk of complications associated with diabetes. We decided to assess the Glycemic Variability (GV) in patients with type 2 diabetes with OSAS and in controls. We also correlated the respiratory disturbance indices with glycemic variability indices. Methods: After fulfilling the inclusion and exclusion criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Kurosawa et al found a significant and positive correlation between AHI and NREM-AHI with SD [23], another index of GV. Khaire et al reported that night CV% and MAGE between 10 pm and 6 am were significantly higher in 10 patients with OSA compared with those in 10 patients without OSA [24]. In the present study, the values of various markers of GV (e.g., SD and CV) during sleep, in addition to TIR, HBGI, and MDP, were higher in patients with OSA than those in the healthy control group.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…Kurosawa et al found a significant and positive correlation between AHI and NREM-AHI with SD [23], another index of GV. Khaire et al reported that night CV% and MAGE between 10 pm and 6 am were significantly higher in 10 patients with OSA compared with those in 10 patients without OSA [24]. In the present study, the values of various markers of GV (e.g., SD and CV) during sleep, in addition to TIR, HBGI, and MDP, were higher in patients with OSA than those in the healthy control group.…”
Section: Discussionsupporting
confidence: 40%
“…Kurosawa et al found a significant and positive correlation between AHI and NREM-AHI with SD [ 23 ], another index of GV. Khaire et al reported that night CV% and MAGE between 10 pm and 6 am were significantly higher in 10 patients with OSA compared with those in 10 patients without OSA [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not find a significant association between sleep midpoint and mean glucose value or percentage of TIR/TAR/TBR, attention must be paid to circadian‐related variation of glycaemia because greater glycaemic variability has been related to cardiovascular complications in T2D patients 33 . Preliminary evidence shows that severity of obstructive sleep apnoea, a possible trigger of nocturnal glycaemic fluctuations, has a U‐shaped association with chronotype 34,35 . Moreover, a later timing of food consumption in the nights with a postponed sleep midpoint might be another reason behind greater glucose variation during sleep.…”
Section: Discussionmentioning
confidence: 62%
“…Pathologically, OSAS is characterized by intermittent hypoxia and consequent activated inflammation, oxidative stress, and sympathetic system, all of which are involved in the pathogenesis of CAD [ 7 , 8 ]. Previous reports have shown that OSAS confers an increased risk of CAD, particularly in the high-risk population, such as those with hyperlipidemia, diabetes, and hypertension [ 9 – 11 ]. Indeed, the prevalence of OSAS in patients with CAD is estimated 40–60% [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%